Effect of cerebral microhemorrhages on neurocognitive functions in patients with end-stage renal disease. (July 2021) - Atay, Musa; Alkan, Alpay; Toprak, Huseyin; Halac, Gulistan; Erkoc, Reha
Background: Death is the most serious complication of intracerebral hemorrhage. Microbleeding can be a precursor of intracerebral hemorrhage. Susceptibility weighted imaging (SWI) should be included in imaging protocols for some specific groups such diabetic hemodialysis patients in terms of prediction of macrohemorrhages. Purpose: To investigate intracerebral microbleeding in hemodialysis patients and the correlation between microbleeding and neurocognitive impairment. Material and Methods: Forty-nine hemodialysis cases were involved in the study. Locations of microbleeding, correlation between microbleeding and hypertension, diabetes mellitus (DM), age, and duration of dialysis were analyzed. Standardized mini-mental test was performed. The tested cases were divided into two groups: intracerebral microbleeding (group 1, n = 26) and without intracerebral microbleeding (group 2, n = 17). Results: Incidence of microbleeding and macrohemorrhage was noted as 59% and 14%, respectively, in all cases. All macrohemorrhagic cases also have microbleeding. In group 1, neurocognitive impairment was detected in 10 (38.4%) cases: six and four cases with moderate and mild impairment, respectively. In group 2, neurocognitive impairment was detected in 2 (11.7%) cases, both with mild impairment. A significant positive correlation was detected between microbleeding and neurocognitive impairment ( P  = 0.031). Although there was no correlation between attention disorder and microbleeding, a positive correlation was detected between close memory impairment and microbleeding ( P  = 0.027). A positive correlation was detected between DM and microbleeding ( P  = 0.027). Conclusion: In hemodialysis patients, microbleeding can be a cause of neurocognitive impairment which will be important for guide to treatment protocols. SWI should be included in the imaging protocol of diabetic hemodialysis patients with neurocognitive deterioration.